Single-Leg Assessment of Postural Stability After Anterior Cruciate Ligament Injury: a Systematic Review and Meta-Analysis - Tim Lehmann; Linda Paschen; Jochen Baumeister (SpringerOpen, 2017)
Abstract Background Previous reports of single-leg assessment demonstrated functional deficits in postural stability following anterior cruciate ligament (ACL) injury. However, quantified measures describing postural stability vary among investigations and results seem not to be clear. The first aim of this systematic review was to quantify postural deficits in eyes open single-leg stance in patients after ACL injury. Moreover, the second aim was to examine the potential of traditional center of pressure (CoP) measures in order to distinguish postural stability between ACL patients and healthy controls. Methods A systematic literature search in the databases PubMed and Scopus was conducted from their inception to December 2016 to identify relevant articles. Eligibility criteria were limited to controlled trials of eyes open static single-leg stance on a force or pressure plate recording CoP measures in patients after ACL injury. Results Eleven studies were included, involving a total of 329 ACL-injured and 265 control subjects. Random-effects meta-analysis showed significantly increased sway magnitudes (SMDwm = 0.94, p = 0.003) and velocities (SMDwm = 0.66, p = 0.0002) in the ACL group compared to the healthy controls. Sway magnitude in anteroposterior (SMDwm = 0.58, p = 0.02) and mediolateral (SMDwm = 1.15, p = 0.02) direction were significantly increased in ACL patients. No differences were found for the non-injured side. Similarly, no differences have been observed among ACL patients between the injured and non-injured side for sway velocity, while sway magnitude significantly differed (SMDwm = 0.58, p = 0.05). Conclusions The findings of this systematic review and meta-analysis demonstrated decreased postural stability in individuals with ACL injury. Sway magnitude and velocity were significantly increased in the ACL group compared to the healthy controls. Although the included research still exhibited considerable heterogeneity, it may be proposed that fundamental CoP measures are suitable to differentiate patients after ACL injury and healthy controls with respect to postural stability in eyes open single-leg stance.